The Existence of Perfect Equilibria in a Model of Growth with Altruism between Generations - Leininger, Wolfgang (Review of Economic Studies, 1986)
An intertemporal model of consumption and bequest behaviour is specified and analysed as a game between generations. The main feature of this game is that no a priori restrictions (like linearity) are placed on the strategy choice of generations. The paper gives an existence proof for perfect (Nash) equilibria in finite and infinite horizon versions of the model and determines characteristic properties of equilibrium strategies. The main result is to demonstrate existence of stationary perfect equilibrium if the time horizon is infinite.